CREATIVE THINKING AS A PSYCHOLOGICAL FACTOR DETERMINING STUDENTS' LEARNING CHARACTERISTICS - Gazibekova Gulavza Ergashevna (Web of Journals Publishing, 2023)
In the article, students are considered as future specialists, the theoretical issues of creative thinking and creativity formation in them were clarified, and experimental data were presented.
Keywords: student period, creative thinking, creativity, scientific, theoretical, activity.